La littérature au secret: Une filiation impossible: Книжевноста тајно: Едно невозможно сродство - Derrida, Jacques; Angelovska, Despina (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Jacques Derrida | Жак Дерида Title (French): La littérature au secret: Une filiation impossible Title (Macedonian): Книжевноста тајно: Едно невозможно сродство Translated by (French to Macedonian): Despina Angelovska | Деспина Ангеловска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 73-102 Page Count: 29 Citation (French): Jacques Derrida, “La littérature au secret: Une filiation impossible,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 73-101. Citation (Macedonian): Жак Дерида, „Книжевноста тајно: Едно невозможно сродство“, превод од француски Деспина Ангеловска, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 73-102.